The Supervision of Village Fund Management to Prevent Corruption - Dewi Kania Sugiharti; Zainal Muttaqin; Rully Herdita Ramadhani (Faculty of Law, Universitas Padjadjaran, 2021)
Indonesian village government is required to carry out its duties properly. The village government has an obligation to understand legal instruments in many laws and regulations. The legal instruments serve as a guideline to carry out the accountability of the village officials to execute programs that use village funds. Unfortunately, the requirements have not been materialized due to the increasing corruption involving village heads who abused village funds. The study aims to find out the form of accountability of the village head as the power holder of village fund users when there are allegations of village fund corruption and the supervisory function that can be carried out by the Village Consultative Body (BPD – Badan Perwakilan Desa) in preventing of village funds to be corrupted by the village head. The study shows that the legal instruments and implementation of the use of village funds are basically in accordance with the principles and principles of managing state finances, even though the arrangements are separate from the provisions on regional government, where these arrangements and management must be under the objectives of state life as regulated in the 1945 Constitution. Moreover, the form of accountability of the village head regarding the use of village funds refers to the guidelines stipulated in the legal instrument. Still, when the alleged corruption of village funds committed by the village head is proven, the case is resolved according to the criminal law provisions. The supervisory function by the BPD in the management of village funds by the village apparatus is carried out as a form of increasing prosperous village communities. However, the supervision is still weak due to political interests between the village apparatus and the BPD institution in the institutional position of the village government. We can conclude that legal instruments are essential as a guide in managing village funds, including accountability for the use of village funds. In addition, the supervisory function in village management has an important role, especially in preventing the misuse of village funds, leading to corruption allegations.DOI: https://doi.org/10.22304/pjih.v8n3.a3